Serum enzymes levels and influencing factors in three indigenous Ethiopian goat breeds - Tibbo, Markos; Jibril, Y.; Woldemeskel, M.; Dawo, F.; Aragaw, K.; Rege, J.E.O. (Springer, 2008)
Serum enzymes were studied in 163 apparently healthy goats from three indigenous goat breeds of Ethiopia. The effect of breed, age, sex and season on alanine aminotransferase (ALT) / glutamic pyruvic transaminase (GPT), aspartate aminotransferase (AST) / glutamic oxalacetic transaminases (GOT), alkaline phosphatase (ALP) and acid phosphatase (AcP) levels was assessed. The mean serum enzymes levels of the indigenous Arsi-Bale, Central Highland and Long-eared Somali goat breeds ranged from 14.0-20.2 i L-1 for ALT/GPT, from 43.2-49.3 i L-1 for AST/GOT, from 83.7-98.8 i L-1 for ALP, and from 2.99-4.23 i L-1 for AcP, were within the normal range for goats elsewhere. Breed had significant influence on AST/GOT values. Sex had significant effect on ALT/GPT for Arsi-Bale goats with higher values in males than females. Age was significant on all serum enzymes studied in the Arsi-Bale goats and on ALP in the Central Highland goats. Season had significant influence on all serum enzymes except for ALT/GPT in the Arsi-Bale goats. The serum enzyme levels of these indigenous goat breeds can be used as normal reference values for Ethiopian goat breeds adapted to similar agro-ecology and production system.